LIFESTYLE FACTORS ASSOCIATED WITH THE RISK OF PROSTATE CANCER AMONG PAKISTANI MEN - Mahmood, Shahid; Qasmi, Ghazia; Ahmed, Ashfaq; Kokab, Farkhanda; Zahid, Mohammad Farhan; Afridi, Mohammad Imtiaz; Razzaq, Anjum (Journal of Ayub Medical College Abbottabad, 2012)
Background: Age-adjusted incidence of prostate cancer in Pakistan is 5.3 per 100,000 which is relatively low compared to other Asian countries, but increasing numbers of cases are being reported. Data on risk factors associated with prostate cancer risk among Pakistani men are sparse. The objective of this study was to identify lifestyle factors associated with the risk of prostate cancer in Pakistani men. Methods: An unmatched case-control study was conducted in Lahore from February to October 2011. The study enrolled 195 histologically confirmed cases of adenocarcinoma of prostate from Shaukat Khanum Memorial Hospital and Institute of Nuclear Medicine and Oncology Lahore (INMOL) and Lady Reading Hospital, Peshawar, using purposive sampling technique. A total of 390 hospital controls were selected using convenient sampling technique from different teaching hospitals of Lahore after screening with prostate specific antigen levels. A semi-structured interview form was used to collect data through face-to-face interviews. Odds ratio was used as a measure of strength of association and was calculated using unconditional logistic regression. Results: Farmers were found to be at higher odds of prostate cancer (OR=19.76, 95% CI=5.51- 70.80, p<0.001). No significant association was found with marital status, ethnic background, religious affiliation and consanguineous marriages. Level of physical activity was inversely associated with prostate cancer risk (OR=0.05, 95% CI=0.01-0.26, p<0.001). Positive association was found with increased red meat consumption (OR=11.82, 95% CI=2.88-48.54, p=0.001) and dairy products intake (OR=11.76, 95% CI=4.23-32.67, p<0.001). Conclusion: Red meat consumption, higher dairy products intake and working as farmers are strongly associated with increased odds of prostate cancer among Pakistani men. Keywords: Prostate, Lifestyle, Risk, Red meat, Dairy product, Farmer, Cancer